USING COAL AS A PRESSURE INSTRUMENT OR ENERGY WEAPON - Teodora LAZAR; Mila Ilieva OBRETENOVA; Marius Daniel MARCU; Adina TATAR; Nicolae Daniel FITA; Dragos PASCULESCU (Fiabilitate şi Durabilitate)
The emergence of energy dynamism around the world manifested by the lack of finite primary energy resources (oil, natural gas, coal and uranium) and/or electricity to final consumers and the wish of the world's major energy powers to own and control the entire world energy chain for the purpose of using primary energy resources or electricity as a possible energy weapon or pressure instrument in the context of blackmail and profitability, it makes this paper of great importance and relevance, especially in the new context of military instability on the background and due to energy causes. The lack of supply of primary energy resources or electricity to final consumers leads to the triggering of societal crises with possible military escalation and can cause States of societal imbalance bringing extreme damage to the safety of the citizen, industry, national economy and, implicitly, national security. In this context, the energy security of a state becomes an important pillar of national, regional and global security, bringing safety, stability and well-being to consumers, as well as a cause of civil and/or armed conflicts.